(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2015)
Gene therapy of cancerous diseases provides new means of curing patients with oncologic illnesses. There are several approaches in treating cancer by gene therapy. Most commonly used methods are: cancer immunogene therapy, suicide gene therapy, application of tumor-suppressor genes, antiangiogenic therapy, mesenchymal stem cells used as vectors, gene directed enzyme/prodrug therapy and bacteria used as anti-cancer agents. Cancer gene immunotherapy uses several immunologic agents for the purpose of explaining effective anti-tumor immune response. Another method is suicide gene therapy, based on introducing viral or bacterial agents to tumor cells, allowing the conversion of a non-toxic compound to a lethal medication. The application of intact suppressor genes to cancer cells will avert their neoplastic behavior and will induce tumor regression. Inhibition of angiogenesis is also a promising strategy for treating oncologic patients. Mesenchymal stem cells can also be used as vectors in targeted gene therapy. An increasing list of experimental evidence shows, that therapeutically modified mesenchymal stem cells in “gene directed enzyme/prodrug therapy” can attack cancer tissue can kill tumor cells, cancer stem cells included. Bacteria are used as anti-cancer agents independently of in combination with conventional therapeutic methods.